Study on the Lagging Support Mechanism of Anchor Cable in Coal Roadway Based on FLAC3D Modified Model - Xiangyu Wang; Guanghui Wang; Bowen Wu; Shuaigang Liu (Advances in Civil Engineering)
Aiming at the broken failure of anchor cable in the mining roadway roof during the mining process, the lagging support scheme of anchor cable is proposed. Based on the results of indoor anchor cable pull-out test, the Cable element in FLAC3D is modified to realize the extension breaking of anchor cable in the calculation process. Furthermore, the minimum principal stress and volume strain rate mutation point are used as the failure criteria of the anchor cable. Through the comparative analysis of five anchor cable lagging support schemes of 6208 transport tunnel in Wangzhuang Mine Coal, the results demonstrate that the lagging support reduces the initial support resistance of the supporting structure. With the increase of lagging time, the ability of anchor cable to adapt to deformation increases gradually. When the lagging time reaches the gentle area of roadway deformation, its ability to adapt to deformation remains stable. Finally, it was determined that the support should start at 10–15 m of the anchor cable lagging head of the 6208 transport tunnel. Industrial tests show that the lagging support scheme ensures that the anchor cable can withstand a certain deformation, and the support body has no broken failure, which effectively controls the large mining-induced deformation of surrounding rock.